The Impact of High- and Low-Preference Stimuli on Vocational and Academic Performances of Youths with Severe Disabilities - Graff, Richard B (Society for the Experimental Analysis of Behavior, 2006)
Pictorial and tangible paired-stimulus preference assessments were compared with 4 adolescents with developmental disabilities. In the tangible assessment, two stimuli were placed in front of the participant on each trial; in the pictorial assessment, two line drawings were placed in front of the participant on each trial. Approach responses were recorded for each assessment. The assessments generated similar preference hierarchies for all participants. Reinforcer assessments confirmed that response rates were higher when access to high-preference items was available than when low-preference items were available. Implications for assessing preferences and selecting items to be used in training programs are discussed.